Xin’anjiang Nested Experimental Watershed (XAJ-NEW) for Understanding Multiscale Water Cycle: Scientific Objectives and Experimental Design - Ke Zhang; Yunping Li; Zhongbo Yu; Tao Yang; Junzeng Xu; Lijun Chao; Jin Ni; Liutong Wang; Yun Gao; Yuzhong Hu; Zuoding Lin (Engineering, 2022)
This paper presents the background, scientific objectives, experimental design, and preliminary achievements of the Xin’anjiang nested experimental watershed (XAJ-NEW), implemented in 2017 in eastern China, which has a subtropical humid monsoon climate and a total area of 2674 km2. The scientific objectives of the XAJ-NEW include building a comprehensive, multiscale, and nested hydrometeorological monitoring and experimental program, strengthening the observation of the water cycle, discovering the spatiotemporal scaling effects of hydrological processes, and revealing the mechanisms controlling runoff generation and partitioning in a typical humid, hilly area. After two years of operation, preliminary results indicated scale-dependent variability in key hydrometeorological processes and variables such as precipitation, runoff, groundwater, and soil moisture. The effects of canopy interception and runoff partitioning between the surface and subsurface were also identified. Continuous operation of this program can further reveal the mechanisms controlling runoff generation and partitioning, discover the spatiotemporal scaling effects of hydrological processes, and understand the impacts of climate change on hydrological processes. These findings provide new insights into understanding multiscale hydrological processes and their responses to meteorological forcings, improving model parameterization schemes, and enhancing weather and climate forecast skills.